2017
DOI: 10.1001/jamadermatol.2017.3029
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Systemic Agents for the Treatment of Pediatric Psoriasis

Abstract: IMPORTANCE Use of systemic therapies for moderate to severe psoriasis in children is increasing, but comparative data on their use and toxicities are limited.OBJECTIVE To assess patterns of use and relative risks of systemic agents for moderate to severe psoriasis in children. DESIGN, SETTING, AND PARTICIPANTSA retrospective review was conducted at 20 centers in North America and Europe, and included all consecutive children with moderate to severe psoriasis who used systemic medications or phototherapy for at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 31 publications
5
91
1
4
Order By: Relevance
“…Although the use of DMF in the paediatric population is off-label, there are numerous case reports, case series and unpublished clinical experience to suggest that FAEs may be an effective treatment option for children and adolescents if a systemic therapy is indicated. [31][32][33][34][35] A German multicentre, retrospective study on the efficacy and safety of long-term use of FAEs in children and adolescents showed that FAEs were often used successfully in clinical practice as off-label therapy. 36 Trials of DMF in paediatric populations and for more moderate disease are ideally needed.…”
Section: Patient Profile and Selectionmentioning
confidence: 99%
“…Although the use of DMF in the paediatric population is off-label, there are numerous case reports, case series and unpublished clinical experience to suggest that FAEs may be an effective treatment option for children and adolescents if a systemic therapy is indicated. [31][32][33][34][35] A German multicentre, retrospective study on the efficacy and safety of long-term use of FAEs in children and adolescents showed that FAEs were often used successfully in clinical practice as off-label therapy. 36 Trials of DMF in paediatric populations and for more moderate disease are ideally needed.…”
Section: Patient Profile and Selectionmentioning
confidence: 99%
“…Moderate-to-severe cases of psoriasis may either require general treatments, such as phototherapy, or require conventional systemic treatments such as acitretin, ciclosporin, methotrexate or fumaric acid esters. 5,6 However, data are sparse on the efficacy and toxicity of systemic agents in the paediatric population. [6][7][8] Standardised guidelines are lacking, and few clinical trials have been conducted in children.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 However, data are sparse on the efficacy and toxicity of systemic agents in the paediatric population. [6][7][8] Standardised guidelines are lacking, and few clinical trials have been conducted in children. 5,[9][10][11] Targeted therapies, including tumour necrosis factor alpha blockers (anti-TNFa agents) and ustekinumab, have recently been shown to be effective and safe as therapies for childhood psoriasis in controlled trials.…”
Section: Introductionmentioning
confidence: 99%
“…23 Biologic treatment of psoriasis in children is reported as less likely to result in adverse events or in treatment discontinuation compared with MTX. 24 The current analysis reports results from the first randomized 52-week controlled trial, comparing the efficacy and safety of a biologic treatment, ADA (Humira â , AbbVie Inc., North Chicago, IL, U.S.A.), a recombinant fully human monoclonal antibody directed against TNF-a, with the active comparator MTX, in children with severe plaque psoriasis. Results from the first three periods of this trial have been reported.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…Results of long‐term treatment of children with moderate‐to‐severe psoriasis have been published for open‐label etanercept, and for ustekinumab vs. placebo . Biologic treatment of psoriasis in children is reported as less likely to result in adverse events or in treatment discontinuation compared with MTX …”
mentioning
confidence: 99%